Provinols™, a Polyphenolic Extract of Red Wine, Inhibits In-Stent Neointimal Growth in Cholesterol-Fed Rabbit - Meyer Elbaz; Gérald Roul; Ramaroson Andriantsitohaina (MDPI AG, 2024)
Background/Objectives: Epidemiological studies indicate a potential correlation between the consumption of polyphenols and a reduced risk of developing cardiovascular disorders. The present study investigates the potential of a red wine polyphenol oral extract, Provinols™, to reduce neointimal hyperplasia following angioplasty in a hypercholesterolemic rabbit model. Methods: New Zealand white rabbits were fed 1% cholesterol-enriched chow for a period of eight weeks prior to the induction of iliac balloon injury and subsequent stent placement. Following the implantation of the stent, Provinols™ (20 mg/kg/day) or an identical placebo was administered orally for a period of four weeks in a randomized manner. Twenty-eight days following the stenting procedure, the arteries were harvested after euthanasia and subjected to histology assignment analysis. Results: The administration of Provinols™ did not result in a statistically significant change in either blood pressure or plasma cholesterol levels. However, Provinols™ treatment led to a notable reduction in the growth of the intima within the stented area, as well as a reduction in the thickness and surface area of the intima. It is of note that treatment with Provinols™ was associated with a reduction in the accumulation of fat within the arteries and a diminished inflammatory response to injury. Conclusions: The findings demonstrate that oral administration of Provinols™ has the potential to reduce in-stent neointimal growth and lipid deposition, likely due to its anti-inflammatory properties in iliac arteries from hypercholesterolemic rabbits. Additionally, these findings provide an evidence-based rationale for the potential therapeutic benefits of plant-derived polyphenols in the prevention of restenosis associated with stent placement.